Effect of support on the performance of PtRu-based catalysts in oxidative steam reforming of ethanol to produce hydrogen - Tang, Chih-Wei; Liu, Chiu-Hung; Yu, Shen-Wei; Wang, Chen-Bin (Frontiers in Chemistry, 2022)
Oxidative steam reforming of ethanol (OSRE) to produce hydrogen has been investigated over a series of supported PtRu catalysts, with different supports. Bimetallic PtRu-based catalysts were prepared by the impregnation method using H2PtCl6 and RuCl3 as precursors. Six supports (reducible oxides of ZrO2, CeO2, and Co3O4, and irreducible oxides of ZnO, Al2O3, and NiO) were chosen to fabricate bimetallic catalysts. The catalytic performance of the OSRE reaction in the series of PtRu-based samples was evaluated using a fixed-bed flow reactor under atmospheric pressure. In front reaction, the catalyst was pre-activated by reduction under 200°C for 3 h. The gas hourly space velocity was adjusted at 66,000 h−1, and the optimal molar ratios of the H2O/EtOH and O2/EtOH feeds were 4.9 and 0.44, respectively. The results indicated that the PtRu supported on the ZrO2 and CeO2 exhibited superior catalytic performance in the OSRE reaction under a low temperature (a TR of approximately 320°C) for producing the main products of H2 and CO2 with lower CO and CH4 by-products. Also, it was quite stable during a long time evaluation; the maximum YH2 maintained at 4.5–4.2, and the CO distribution approached 3.3–3.5 mol% around 84 h test at 340°C over the PtRu/ZrO2 catalyst.